Production under uncertainty: a characterization of welfare enhancing and optimal price caps - Veronika Grimm; Gregor Zoettl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2008)
We analyze the effect of price caps on equilibrium production and welfare in oligopoly under demand uncertainty. We find that high price caps always increase production and welfare as compared to the situation without price cap. Price caps close to marginal cost may lead to zero production, depending on the nature of uncertainty. We characterize the optimal price cap and show that typically, the optimal price cap is bounded away from marginal cost.
Keywords: D43; L13; D41; D42; D81; 330; Demand uncertainty; Cournot competition; price caps; Anreizregulierung; Produktion; Entscheidung bei Unsicherheit; Nachfrage; Oligopol; Nash-Gleichgewicht; Wohlfahrtseffekt; Theorie